1984
DOI: 10.1136/bmj.288.6416.513
|View full text |Cite
|
Sign up to set email alerts
|

Passive-active immunisation of neonates of HBsAg positive carrier mothers: preliminary observations.

Abstract: Screening of pregnant women for hepatitis B surface antigen (HBsAg) in three areas of Holland led to the identification of HBsAg carriers, 20 of whom were subsequently delivered. Within two hours after birth all infants received hepatitis B immune globulin (0-5 ml/kg body weight) and, after randomisation, hepatitis B vaccine (10 ,tg) was given either at 0, 1, and 2 months of age or at 3, 4, and 5 months of age, the latter concomitantly with DPTP vaccination. Eighteen infants complying with the protocol were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…All blood samples positive for hepatitis B surface antigen were also tested for hepatitis B e antigen and its antibody (Abbott Laboratories). An additional blood sample from the women positive for hepatitis B surface antigen was obtained at delivery to verify the eligibility of their infants for passive-active immunisation 4 5 6. The presence of hepatitis B surface antigen in expectant mothers was checked in the delivery rooms in Rotterdam.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All blood samples positive for hepatitis B surface antigen were also tested for hepatitis B e antigen and its antibody (Abbott Laboratories). An additional blood sample from the women positive for hepatitis B surface antigen was obtained at delivery to verify the eligibility of their infants for passive-active immunisation 4 5 6. The presence of hepatitis B surface antigen in expectant mothers was checked in the delivery rooms in Rotterdam.…”
Section: Methodsmentioning
confidence: 99%
“…This study lasted seven years and preliminary results have already been reported 4 5 6. The final results of routine antenatal screening for hepatitis B surface antigen in pregnant women, reported here, led to a proposal for universal screening in the Netherlands; a national programme for such screening was subsequently implemented.…”
Section: Introductionmentioning
confidence: 97%
“…These infants were still susceptible to HBV, and a substantial portion of them will become HBsAg carriers after HBV infection [Beasley and Hwang, 19831. Because of the transient protection yielded by HBIG alone and the inadequate efficacy of hepatitis B vaccine alone (Lee, Hwang, Beasley, unpublished observations, 1985), many investigators have started the regimen of HBIG plus hepatitis B vaccine in blocking perinatal HBV transmission [Wong et al, 1984;Maze1 et al, 1984;Tada et al, 1982;Chung et al, 1985;Kanai et al, 1985;Piazza et al, 1985;Lo et al, 19851. With HBeAg-positive mothers, our government has adopted the policy of giving 0.5 ml of HBIG to the newborns as soon as possible after birth, followed by four doses of hepatitis B vaccine: at 1 week, 5 weeks, 9 weeks, and 12 months of age [The Hepatitis Control Committee and the Epidemiology Division of the Department of Health, 19851.…”
Section: Discussionmentioning
confidence: 97%
“…In view of the present studies and our previous findings (24,25) that antigens become more potent immunogens of T cells in uitro when they are linked to antibodies, the minute contaminating HBsAg in these HBIG preparations may have formed immune complexes that became sufficiently immunogenic to induce host's production of anti-HBs. It was shown in another set of studies that the combined administration of HBsAg vaccine and HBIG to newborns of chronic HB carrier (HBeAg+) mothers was far more effective than either the vaccine or HBIG alone in preventing perinatally transmitted HBV infection and the chronic carrier state (53)(54)(55)(56)(57)(58)(59)(60). The effects of HBIG are generally ascribed to its role in passive immunization.…”
Section: Discussionmentioning
confidence: 99%